GOOGLE TRANSLATE: A TOOL FOR TEACHING RECOUNT PARAGRAPH WRITING TO EFL STUDENTS - Suparwoto Sapto Wahono; Siti Afifatur Rohmah (Tell-us Journal)
This study investigated the effectiveness of using Google Translate as a tool to teach recount text writing to EFL (English as a Foreign Language) students in the second grade of MTs At-Thohiriyah, a junior high school in Jember, East Java, Indonesia. The study, conducted using a qualitative descriptive approach, analyzed data collected through classroom observations, interviews with teachers and students, and document analysis. The findings revealed that Google Translate was an effective tool for teaching recount text writing, helping students understand the structure of recount texts, expand vocabulary, improve grammatical accuracy, and increase motivation and interest in learning. The study also explored the challenges and limitations of using Google Translate in language learning and provided recommendations for educators seeking to integrate technology into their language teaching practices.